Songbird tap dancing produces non-vocal sounds*. Issue 2 (4th May 2017) - Ota, Nao; Gahr, Manfred; Soma, Masayo
Abstract: Vocalizations have been elucidated in previous songbird studies, whereas less attention has been paid to non-vocal sounds. In the blue-capped cordon-bleu ( Uraeginthus cyanocephalus ), both sexes perform courtship displays that are accompanied by singing and distinct body movements (i.e. dance). Our previous study revealed that their courtship bobbing includes multiple rapid steps. This behaviour is quite similar to human tap dancing, because it can function as both visual and acoustic signals. To examine the acoustic signal value of such steps, we tested if their high-speed step movements produce non-vocal sounds that have amplitudes similar to vocal sounds. We found that step behaviour affected step sound amplitude. Additionally, the dancing step sounds were substantially louder than feet movement sounds in a non-courtship context, and the amplitude range overlapped with that of song notes. These results support the idea that in addition to song cordon-bleus produce acoustic signals with their feet.